Instillation Of Pancasila Values Through Social Science Education - Maharani, Sinta; Nandayana, Yasmin; Siddik, Ihsan Abdurrahman; Mudzalifah, Najwa; Wahyunengsih, Wahyunengsih (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was to analyze the instillation of Pancasila values through social sciences education which has an important role in instilling Pancasila values in students. Social studies learning materials such as history, geography, economics and sociology are full of the noble values of Pancasila such as divinity, humanity, unity, democracy and justice. Instilling Pancasila values can be done through various learning strategies that actively involve students, such as group discussions, simulations, case studies, and learning projects that contain Pancasila values. The use of interesting and contextual learning media can also increase understanding and internalization of Pancasila values. Social studies teachers act as role models in implementing Pancasila values. The involvement of parents and the community is also very important in supporting the installation of Pancasila values in the school environment. By effectively integrating Pancasila values in social studies learning, it is hoped that students will not only gain academic knowledge, but also build character in accordance with the noble values of the Indonesian nation. The findings of this research are useful for social studies teachers or lecturers to explore how to instill Pancasila values through social studies education, so that students truly have the spirit of Pancasila to apply it in everyday life.